Development And Evaluation Of Analgesic Polyherbal Formulation Containing Some Indigenous Medicinal Plants - PRAVIN V. GOMASE; PRITI S. SHIRE; SAYYED NAZIM; AMOL B. CHOUDHARI (International Journal of Pharma and Bio Sciences, 2011)
The present study explores the Polyherbal formulation for Analgesic activity of ethanolic leaves extracts of Momardica charantia Linn and Azadirachta indica A. Juss agaist experimental model of Eddy’s hot plate method And Heat conduction method response in rats. The effective dose of the extract for analgesic activity was calculated from dose-response curve by using the Eddy’s hot plate method And Heat conduction method response in rats. Polyherbal suspensions were prepared by the trituration method using a suspending agent and ethanolic dried extract of leaves. The formulation of Momardica charantia Linn and Azadirachta indica A. Juss were evaluated for analgesic activity. In both of Eddy’s hot plate method And Heat conduction method response in rats writhing response method; the intraperitoneal administration of formulation F1 and F2 induced a significant analgesic activity in a dose-dependent manner respectively in the rats. Formulation F1 has shown significant analgesic effect than the F2 with compare of Diclofenac sodium as a standard drug. The plant may have the phytoconstituents which inhibit cyclooxygenase enzyme or act on central opioid receptors.